Lead contamination analysis of perovskite modules under simulated working conditions. (15th September 2021) - Wan, Jingwei; Yu, Xinxin; Zou, Junjie; Li, Kangchuang; Chen, Li; Peng, Yong; Cheng, Yi-bing
Highlights: Evaluated influences of Pb in perovskite modules on our environment. Well encapsulation methods minimized lead contaminate. The maintenance standards of solar panels should be rescheduled. Abstract: Perovskite solar cells (PSCs) are expected to become the most commercial potential candidate of photovoltaic (PV), owing to the uninterrupted enhancement of performance and relatively low production cost. However, Pb, which is irreplaceable for high-quality perovskite, is toxic and will cause contamination to the environment. Therefore, it is significant to make an accurate assessment of Pb leakage in perovskite modules (PMs) and its impact on the environment. In this paper, Pb leaking behaviors in PMs under simulated real working conditions were investigated. Regarding to the results, a widely used "sandwich" encapsulation (SE) method (using polyolefin and polyisobutylene as encapsulants) could effectively prevent Pb in PMs from leaking even when PMs were seriously broken. In addition, only 0.029% Pb in PMs leaked out when cracked PMs were fully washed by a large quantity of acid rainwater (pH = 5.6) at 85 ℃ for more than 4 h. Even if all polluted water were fully dispersed into soil 5 cm underneath perovskite solar panels, the Pb in the soil increased by 3.4 ppm only, which is acceptable according to most soil environmental quality risk control standards. This work provides important guidance for the more reasonable application of PMs.